Identifying Downregulation of Autophagy Markers in Kawasaki Disease - Fu-Chen Huang; Ying-Hsien Huang; Ho-Chang Kuo; Sung-Chou Li (MDPI AG, 2020)
Kawasaki disease (KD) is the most common cause of heart disease acquired in childhood. Even if treated with high-dose intravenous immunoglobulin G (IVIG) at the early stage; children are still at risk of developing coronary artery lesions. Accumulating evidence suggests that autophagy is enhanced in various heart diseases. Evaluating the pathogenic role of autophagy in KD and coronary artery lesions (CAL) may aid in identifying a potential therapeutic target for the treatment or prevention of the disease. Blood samples were obtained from 20 children with KD at the onset of disease and 21 days after IVIG therapy. Twenty children with other causes of febrile disease and 20 healthy children were included as controls. Total RNA was extracted from white blood cells; and autophagy-related gene mRNA expression levels were measured using real-time polymerase chain reaction. The patients with KD had downregulated levels of LC3B mRNA (0.50 ± 0.06 vs. 1.67 ± 0.15; p < 0.001), BECN1 mRNA (0.70 ± 0.08 vs. 1.43 ± 0.23; p < 0.05), and ATG16L1 mRNA (0.28 ± 0.04 vs. 0.96 ± 0.16; p < 0.01) compared to the febrile control group. The values of these parameters all increased significantly 21 days after the IVIG therapy as follows: LC3B mRNA (1.77 ± 0.29 vs. 0.50 ± 0.06; p < 0.001), BECN1 mRNA (1.67 ± 0.36 vs. 0.70 ± 0.08; p < 0.05), and ATG16L1 mRNA (2.96 ± 0.43 vs. 0.28 ± 0.04; p < 0.001), while the level of ATG16L1 mRNA persists low in KD patients with CAL. Our results showed the autophagy-related genes expressions in KD and their change after IVIG administration. This suggests that autophagy may have a protective effect on KD.